Research and Critical Review of Iqbal Fahmi by Dr. Parveen Shaukat Ali - Javed, Tariq; Tasleem, Asifa (sourcecoder, 2023)
In the article under review titled "Dr. Parveen Shaukat Ali’s Iqbal Fahmi: A Research and Critical Review" the Iqbal Fahmi of Dr. Parveen Shaukat Ali has been examined and it has been analyzed how far Dr. Parveen Shaukat Ali has succeeded in hashing out Iqbal’s thought. Has she understood Iqbal’s message as correct and had she done the right thing in conveying it to the people or not? In this regard, the text of Dr. Parveen Shaukat Ali has been studied and comprehensively, and the opinions of experts and critics have also been included. A mixed methodology has been used in this study. Dr. Parveen Shaukat Ali is the granddaughter of renowned writer Hakeem Shuja and wife of political scholar Shaukat Ali. She served as a professor in Lahore Women’s College and Forman Christian College Lahore. After retirement, she went to America. Dr. Parveen Shaukat Ali received her PhD degree from Punjab University, Lahore. The title of her paper was "Iqbal’s Philosophy of Politics" In her paper, she has examined the political services of Iqbal and has conclude that Iqbal participated theoretically and practically in the politics of the Indian subcontinent and played a fundamental role in achieving a separate state.